IMPLEMENTASI CODEIGNITER FRAMEWORK DALAM APLIKASI E-VOTING PEMILIHAN KETUA KELAS BERBASIS WEBSITE - Syalis Ibnih Melati Istini; Irsan Zuhri Harahap (Asosiasi Dosen Muda Indonesia, 2022)
The rapid development of internet technology is in line with the development of information technology. By using a browser, both mobile and desktop-based devices, information can be obtained easily in a short time. Elections with a voting system are elections that contain judgments or decisions in selecting an object. At present, the general election system for organizations still uses a conventional voting system using ballots which has several weaknesses but these weaknesses can be overcome by implementing electronic voting Information Technology which can be used by all groups or small organizations, and is useful for reducing unnecessary administrative costs. requires ballot papers and reduces time in the vote counting process, based on these problems a literature study is carried out, designing the appearance and flow of the program, implementing the design results into PHP programming language codes structured into the CodeIgniter framework, and conducting application testing. The final results show that the E-voting website application can be used as an alternative during general elections by all organizations that will hold elections. The Prefect Election E-voting website can be accessed via http://evoting3ka06ug.infinityfreeapp.com/.